Refugees and displaced persons with disabilities – from forgotten to vulnerable to valuable - Pearce, E (Refugee Studies Centre, University of Oxford, 2012)
Recent years have seen a growth in debate, learning and advocacy in the humanitarian sector on the needs and rights of persons with disabilities among displaced populations.